PENGARUH PENDEKATAN KONTEKSTUAL TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN PKn KELAS V SEKOLAH DASAR - Rima Apriliana; Tahmid Sabri; Siti Halidjah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aims to analyze the effect of contextual approaches on student learning outcomes in learning citizenship education in grade V elementary school. The research method used was an experimental, non-equivalent group design type Quasi Experimental form. The study population is all fifth grade elementary school students 56 West Pontianak. The sampling technique uses simple random sampling. The technique used is direct observation and measurement techniques. The data collection tool used is a multiple choice test. The results of data analysis namely, the average score of the control class post-test was 68.06 and the experimental class was 74.83. Based on the results of t-test calculations obtained tcount 2.830> t table 2,000, then Ha is accepted. This shows that there are differences in the learning outcomes of control class students with the experimental class. Calculation of effect size of 0.79 with medium criteria. The conclusion of this research is that there is an effect of the Contextual Approach on Student Learning Outcomes in the Learning of Citizenship Education for Class V Elementary Schools in the medium category. Keywords: Civics Education,Contextual Approach, Learning Outcomes